A hybrid power converter with enhanced switching ripple cancellation - Papadopoulos, Savvas (2017)
As worldwide electricity demand increases, so does the requirement for effective power conversion combining increased efficiency with minimal harmonic pollution at the lowest financial cost. For medium to high voltage grid-connected applications, multilevel converter topologies enabled the use of lower rated and more efficient self-commutated switches. Due to practical limitations, efficient operation of converters with a low number of levels is restricted to low switching frequencies which in turn becomes a limiting factor for the design of smaller passive filters that are required to limit the associated switching harmonics injected in the AC grid.